The Crisis in Curriculum Studies and the Fourth Industrial Revolution: Reconceptualising Knowledge, Equity, and Competence for a New Era - Fomunyam, Kehdinga George (Journal of Posthumanism, 2025)
This article discusses the crisis in curriculum studies, which has been aggravated by the Fourth Industrial Revolution (4IR). Young (2013) argues that prioritising learner-centred methods may neglect powerful knowledge, the specialised understanding needed for critical thinking beyond everyday knowledge. The 4IR, blending the physical, digital, and biological realms through AI and IoT, demands new skills and exposes inequalities such as the digital divide (Fomunyam, 2023). An effective curriculum should redefine literacy to include digital and data literacy, develop the 4 Cs (critical thinking, creativity, communication, collaboration), encourage interdisciplinary learning, and address ethical issues to counter AI biases. To prepare students for the supercomplexity of an unpredictable future, a pedagogy that merges ontology, epistemology, and praxis is recommended, enhancing resilience and adaptability through inquiry-based, agile learning. Solving the curriculum crisis requires combining powerful knowledge with 4IR skills within a decolonised, flexible curriculum focused on cognitive justice and equity.